The Impact of the Tax Cuts and Jobs Act on Foreign Investment in the United States - Matheson, Thornton (IMF Working Papers; Working Paper, 2022)
The 2017 Tax Cuts and Jobs Act (TCJA) sharply reduced effective corporate income tax rates on equity-financed US investment. This paper examines the reform's impact on US inbound foreign direct investment (FDI) and investment in property, plant and equipment (PPE) by foreign-owned US companies. We first model effective marginal and average tax rates (EMTRs and EATRs) by country, industry, and method of finance, and then use those tax rates to calculate the tax semi-elasticities of inbound FDI and PPE investment. We find that both PPE investment and FDI financed with retained earnings responded positively to the TCJA reform, but FDI financed with new equity or debt did not. In country-level PPE regressions, inclusion of macroeconomic controls renders tax rate coefficients insignificant, suggesting that the increase in PPE investment after TCJA was driven by general economic growth. In regressions of FDI financed with retained earnings, however, tax coefficients were robust to inclusion of macroeconomic controls. As the literature predicts, EATRs have a greater impact on cross-border investment than EMTRs. Country-by-industry regressions showed a larger effect of taxes on PPE investment than aggregate country-level regressions, but industry-level tax rates appear to have no effect on earnings retention.